Activating the developmental social role of the Social Solidarity Fund at King Saud University (Proposed template) - Alotiby, Deem Saleem (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aims to identify the reality of the social role of the Social Solidarity Fund at King Saud University in accordance with achieving the university’s objectives in community service and enhancing social responsibility in the work and initiatives of the Fund and adhering to the standards of social responsibility ISO 26000 by submitting a proposed model The content analysis approach was used for official documents and policies, and data collection from the official sources of the Social Solidarity Fund at King Saud University, through two main topics: The first topic: will review the theoretical framework of social responsibility and identify Arab experiences and local experience in the Kingdom of Saudi Arabia for social solidarity funds and analysis. The second topic: Analyzing the reality of social responsibility and the social role of the Social Solidarity Fund at King Saud University, answering the questions of the study and presenting the proposed model for the work of the Fund. The study concluded the most important results: the weakness of the social developmental role of the Social Solidarity Fund, the absence of policies regulating the work of social responsibility in the system and regulations of the Fund, in addition to the lack of understanding of social responsibility and the absence of evaluation of the Fund’s work according to the standards of measuring social responsibility ISO26000. This study recommends applying the proposed model to the Fund’s work, adopting the standard of social responsibility, and activating the developmental role in accordance with the third strategic goal of King Saud University.